Bereavement as A Risk Factor for Depression in The Elderly: An Evidence Based Case Report - Andoko, Dewanto; Handoko, Marshel Timotius; Cipta, Darien Alfa (Fakultas Kedokteran Universitas Pelita Harapan, 2024)
Background: Depression disorder among the elderly population is a serious issue that is often underdetected and undertreated. Depression can lead to functional impairments, which are comparable to or even worse than those in individuals with chronic conditions such as heart and lung diseases. Bereavement is believed to be one of the risk factors for depression in the elderly. This literature search aims to explore bereavement as an etiology of depression in the elderly. Method: A structured search was conducted using the PubMed, Cochrane, and Science Direct databases, using tailored keywords aligned with the clinical question to obtain relevant results. Results: The search and selection process yielded one selected article that was deemed relevant to the case. This article provided a summary of evidence concerning the relationship between bereavement and the emergence of depression diagnosis in the elderly. Conclusion: The results of this systematic review and meta-analysis indicate that bereavement increases the risk of depression in the elderly. However, further studies are still needed to elucidate the mechanisms underlying depression in the elderly.